First case of subcutaneous cystic phaeohyphomycosis due to Phialophora chinensis in a kidney transplant recipient in Martinique - Clément Pruvot; Anne Laure Messagier; Dea Garcia-Hermoso; Fréderic Lebailly; Cédric Aglae; Nicole Desbois-Nogard (Medical Mycology Case Reports, 2023)
We report a case of subcutaneous mycosis in the form of a subcutaneous cyst of the index finger, successfully treated by surgery and posaconazole in an 84-year-old female kidney transplant patient. Intra-operative mycological analysis enabled the diagnosis of Phialophora chinensis phaeohyphomycosis. Phialophora chinensis is an environmental mold recently described in human pathology in cases of chromoblastomycosis. This is the first case of subcutaneous phaeohyphomycosis due to Phialophora chinensis in an immunocompromised patient.